A review of FLT3 inhibitors in acute myeloid leukemia. (March 2022) - Zhao, Jennifer C.; Agarwal, Sonal; Ahmad, Hiba; Amin, Kejal; Bewersdorf, Jan Philipp; Zeidan, Amer M.
Abstract: FLT3 mutations are the most common genetic aberrations found in acute myeloid leukemia (AML) and associated with poor prognosis. Since the discovery of FLT3 mutations and their prognostic implications, multiple FLT3-targeted molecules have been evaluated. Midostaurin is approved in the U.S. and Europe for newly diagnosed FLT3 mutated AML in combination with standard induction and consolidation chemotherapy based on data from the RATIFY study. Gilteritinib is approved for relapsed or refractory FLT3 mutated AML as monotherapy based on the ADMIRAL study. Although significant progress has been made in the treatment of AML with FLT3-targeting, many challenges remain. Several drug resistance mechanisms have been identified, including clonal selection, stromal protection, FLT3-associated mutations, and off-target mutations. The benefit of FLT3 inhibitor maintenance therapy, either post-chemotherapy or post-transplant, remains controversial, although several studies are ongoing. Highlights: Two generations of FLT3 inhibitors have been developed with differences in potency and specificity. Resistance to FLT3 inhibitors may develop by clonal selection, stromal protection, FLT3-associated or off-target mutations. Additional studies are needed to reveal key information regarding FLT3 inhibitors as post-chemotherapy maintenance.